Problem Based Learning (PBL) in Shaping the Character of Students' Hard Work and Discipline Through Classification of Creatures: Pembelajaran Problem Based Learning (PBL) dalam Membentuk Karakter Kerja Keras dan Disiplin Siswa Melalui Materi Klasifikasi Mahluk Hidup - Aqil, Deden Ibnu; Purwanto, Agung; Budi, Setia; Gayatri, Askardiya Mirza; Hudaya, Adeng (Pedagogia : Jurnal Pendidikan, 2022)
The purpose of this study is to find out how the application of learning with problem based learning (PBL) in influencing the character of hard work and student discipline through the material classification of living things. The method used in this study was class VII a number of 25 students in the Nusa Bhakti Junior High School in Depok City as objects in the natural science subject matter classification of living things. Data collection techniques using learning methods and questionnaires / questionnaires. The instrument test uses descriptive analysis, linearity test, homogeneity test and t-paired t-test. The results showed that the value of sig. (2-tailed) is 0.015 <0.05 (α = 5%) that there are differences in students' hard work before and after the use of PBL and sig. (2-tailed) 0.002 <0.05 (α = 5%) ie there are differences in student discipline before and after the use of PBL. Learning with problem based learning (PBL) can improve the character of students' hard work and discipline.